Effect of vitamin D supplementation on pain and physical function in patients with knee osteoarthritis (OA): an OA Trial Bank protocol for a systematic review and individual patient data (IPD) meta-analysis. Issue 4 (23rd April 2020) - Jin, Xingzhong; Antony, Benny; Wang, Xia; Persson, Monica SM; McAlindon, Timothy; Arden, Nigel K; Srivastava, Sudeepti; Srivastava, Rajeshwar; Van Middelkoop, Marienke; Bierma-Zeinstra, Sita MA; Zhang, Weiya; Cicuttini, Flavia; et al.
Abstract : Introduction: Observational data suggest that vitamin D deficiency is associated with the onset and progression of knee osteoarthritis (OA). However, randomised controlled trials (RCTs) to date investigating the efficacy of vitamin D supplementation in knee OA have reported conflicting results. Further research is needed to clarify the effects of vitamin D on patient-reported outcomes and determine whether there are patient subgroups who may benefit from the supplementation. The aim of this individual patient data (IPD) meta-analysis is to identify patient-level predictors of treatment response to vitamin D supplementation on pain and physical function. Methods and analysis: A systematic literature search will be conducted for RCTs of vitamin D supplementation on knee OA. Authors of original RCTs will be contacted to obtain the IPD. The primary outcomes will include long-term (≥12 months) pain and physical function. Secondary outcomes will include medium-term (≥6 months and <12 months) and short-term (<6 months) pain and physical function, as well as patient global assessment, quality of life and adverse events. Potential treatment effect modifiers to be examined in the subgroup analyses include age, gender, body mass index, baseline knee pain severity and physical function, baseline vitamin D level, radiographic stage, presence of bone marrow lesions on MRI, presence of clinical signs of local inflammation and concomitant depressive symptoms. Both one-step and two-step modelling methods will be used to determine the possible modifiable effect of each subgroup of interest. Ethics and dissemination: Research ethical or governance approval is exempt for this study as no new data are being collected. This study will be the first IPD meta-analysis to clarify the effect of vitamin D supplementation on clinical symptoms in different subgroups of patients with knee OA. The findings will be disseminated through peer-review publications and conference presentations. PROSPERO registration number: CRD42018107740.